Gambaran Profil Lipid Pasien Diabetes Melitus Tipe 2 - Oka Kusuma Jaya, I Gede; Sukawana, I Wayan; Sukarja, I Made; Juniari, Ni Made (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
The prevalence of diabetes mellitus (DM) continues to increase and is even predicted to continue to increase, as does Indonesia, which is currently the country with the highest prevalence of DM in Southeast Asia. The most common type of DM currently is type 2 DM, the majority of which is caused by an unhealthy lifestyle, causing insulin resistance. Apart from causing diabetes, insulin resistance also causes dyslipidemia and is one of the most important factors in the occurrence of atherosclerosis which has an impact on the emergence of diabetic ulcers. This study aimed to determine the lipid profile in patients with type 2 diabetes mellitus. The research design used was descriptive with an observational approach. The variable observed in this study was the lipid profile in type 2 DM patients. The sampling technique used was simple random sampling with a sample size of 47 people. The instrument used is a documentation sheet. The research was conducted at the Klungkung Regional General Hospital (RSUD). The data collected was analyzed using descriptive statistics, and the data was then presented in a table. The results of the study showed that the total cholesterol value in type 2 diabetes mellitus sufferers with total cholesterol values above 200 mg/dL was 26,4%, and the LDL value in type 2 diabetes mellitus sufferers with values above 100 mg/dL was 26,3%. The HDL value in type 2 diabetes mellitus sufferers with a value of less than 40 is 13,0%, and the triglyceride value in type 2 diabetes mellitus sufferers with a value of more than 150 mg/dL is 26,1%. Most respondents have a good lipid profile, but there are still respondents whose lipid profile is not within the normal range and are at risk of developing diabetic ulcers.